REVIEW : PENGARUH PEMANASAN GLOBAL TERHADAP INTENSITAS SERANGAN KUTU KEBUL (Bemisia tabbaci Genn ) DAN CARA PENGENDALIANNYA PADA TANAMAN KEDELAI - I Made Indra Agastya; Reza Prakoso Dwi Julianto; Marwoto Marwoto (BUANA SAINS, 2020)
Global warming has changed global, regional and local climate conditions. Global climate change is caused, among others, by the increase in greenhouse gas emissions (GHG) due to various activities that drive the increase in the earth's temperature. Given that climate is a key element in the metabolic system, plant physiology and crop ecosystems, global climate change will adversely affect the sustainability of agricultural development. The impact of global climate change is the increasing population of pests on agricultural crops. One of the soybean pests whose population is increasing due to the increase in air temperature is the Bemisia tabbaci infestation. Increased pest populations of Bemesia tabbaci infestation in soybean crops cause dwarf leaves of dwarf plants and threatens to increase soybean production. Efforts to overcome the impact of global warming is mainly due to increased pest populations, it is necessary to think and seek breakthroughs to anticipate the explosion of pest populations in soybean crops, among others by: the optimization of natural control, physical and mechanical control and cultivation techniques. The combination of techniques or tactics of the optimal component of soybean pest control technology is established on the basis of appropriate information knowledge about soybean pest, ecosystem and socio-economic based on IPM approach.